Risk Factors for Postpartum Weight Retention in Postpartum Women: An Integrative Review - Shanxia Chen; Meiyu Wang; Yue Wei; Zhuangwei Li; Xiaodan Wang; Hui Song (Nursing Open, 2026)
ABSTRACT Aims To summarise and synthesise extant research studies that identify risk factors for the development of postpartum weight retention in postpartum women. Design Integrative review. Review Methods This review was guided by Whittemore and Knafl's methodology. Eleven databases were searched for relevant original studies from database creation to November 25, 2025. Two researchers independently screened articles against the predefined inclusion and exclusion criteria, extracted data, and assessed the quality of the included studies using the Newcastle‐Ottawa Scale. Descriptive summaries and graphical representations were produced for the findings. PROSPERO registration number: CRD42024530948. Results Of 2750 retrieved sources, 26 studies were included in this review. The existing measurement approach failed to assess postpartum weight retention precisely. Overall study quality was moderate ( n = 16), with seven rated as high quality and three as low quality. Risk factors for postpartum weight retention were categorised into three themes, nine subthemes, and 21 risk factors according to the Andersen model, most of which are modifiable. Conclusion The accuracy of postpartum weight retention measurement approaches needs to be examined to provide reliable data. The incidence of postpartum weight retention is unsatisfactory, especially for women in upper‐middle‐income countries. Designing a comprehensive and evidence‐based health management strategy will support minimising risk factors of postpartum weight retention, and high‐quality empirical studies could be conducted to refine the theoretical framework for postpartum weight retention. Implications for Nursing Practice This study suggests that nursing managers should strengthen education and training for nurses, midwives, and postpartum care providers regarding postpartum weight management and regularly assess their ability to evaluate postpartum weight and identify risk factors for postpartum weight retention. These findings may also serve as a reference for nursing researchers in developing risk assessment instruments for postpartum weight retention and optimising predictive models. Reporting Method This review was conducted by following the PRISMA 2020 guidelines for reporting systematic reviews. Patient or Public Contribution No patient or public contribution.